Exploring Various Flavors of Cilok Snacks for Profit: A Small and Medium Enterprises Activity by Students of Indo Global Mandiri University in Support of MBKM - Hidayahtullah, Hafiz; Hertati, Lesi; Asharie, Asmawati; Avini, Terti (International Journal of Social Science and Community Service, 2023)
The MSME activity carried out by Indo Global Mandiri University students, entitled "Exploring Eneka Rasa Cilok Snacks," is a creative initiative that supports the Student Based Internship Program (MBKM). This activity aims to generate profits through variations in taste in making cilok snacks, which are not only a unique culinary product but also make a positive contribution to the student economy. In developing cilok snacks, students are actively involved in various aspects of the business, including production planning, stock management, marketing, and interaction with local traders to obtain raw materials. Apart from creating additional income opportunities for students, this activity also supports the empowerment of local MSMEs and the preservation of traditional culinary delights. Involvement in MBKM activities provides students with in-depth practical experience in managing small and medium enterprises. Exploration of cilok snacks not only creates a positive economic impact, but also promotes innovation, creativity and understanding of the importance of local economic empowerment. Through this initiative, students not only develop their entrepreneurial skills but also contribute to the formation of community networks around campus. Thus, "Exploring Cilok Eneka Rasa Snacks" is a real example of how student MSME activities can be agents of positive change in supporting local economic growth and providing rich practical experience for participants